Perception and Readiness for Electronic Health Records (EHR) Among Medical & Nursing students and Paramedical Staff in Two Medical College Hospitals - Milan, Mayank; Ahuja, Garv; Sharma, Rohit; Keshav, Keshav; Tanya, Tanya; Sharma, Vidisha; Yadav, Alok; Bhati, Shivam; Kumar Garg, Hemant; Brij Mohan, Col. (Journal of Neonatal Surgery, 2025)
Background: Electronic Health Records (EHR) are pivotal in modernizing healthcare delivery. Understanding the perception and readiness of future healthcare professionals is essential for successful implementation. Objective: To assess the awareness, perception, and readiness for EHR adoption among MBBS students, nursing students, and paramedical staff in two medical colleges. Methods: A cross-sectional survey was conducted using a 15-item Likert scale questionnaire. Participants included 100 MBBS students, 50 nursing students, and 100 paramedical staff. Descriptive statistics, mean scores, standard deviations, and group comparisons were analyzed using SPSS. Results: MBBS students demonstrated the highest mean readiness score (4.12 ± 0.68), followed by nursing students (3.87 ± 0.74) and paramedical staff (3.65 ± 0.81). Awareness of EHR and willingness to learn were high across all groups, while concerns about data security and lack of formal training were notable barriers. Conclusion: While overall perception toward EHR is positive, targeted educational interventions and curriculum integration are needed to enhance readiness and address specific concerns among healthcare trainees.